Lazer em família na era digital: um guia interativo para frequentadores do circuito carioca de artes e culturas - Obata, Anna Carolina Bertani (2024)
This master's thesis investigated how Information and Communication Technologies (ICTs), specifically screens such as smartphones, TVs, and computers, transform shared leisure moments between parents and children. Using an exploratory methodology that included a literature review, direct observation, and a questionnaire, the research was based on the studies of Sonia Livingstone and data from the TIC Kids Online Brasil (2023) survey. The results indicated a significant influence of ICTs on family interactions, highlighting the importance of parental mediation in screen use. As a practical contribution, the outcome of this study is a detailed description of the content and layouts of the pages of the Interactive Guide titled O Guia do Pequeno Explorador Carioca, a hybrid leisure experience designed for parents and guardians with children aged 4 to 11 who frequent the Carioca Arts and Cultures Circuit and Nelson Mandela Square in the Botafogo neighborhood of Rio de Janeiro.